2016
DOI: 10.1016/j.bjorl.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effects of bismuth subgallate on the inflammatory process and angiogenesis of the oral mucosa

Abstract: Bismuth subgallate had a negative influence on the healing process, delaying the rate of new vessel formation and optimal wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…86 On the other hand, Kiliç et al (2013) showed general increase in macrophage infiltration on Day 5 post-treatment with glutathione; however, this study lacked quantitative evidence besides H&E staining on the epidermis and lamina propria. 89 Couto et al (2016) studied the effects of applying bismuth subgallate in the buccal wounds of Wistar rat but results found a chronic inflammation status and a possible negative effect leading to delayed healing. 142 Similarly, Ophof et al (2008) stated that treatment with autologous mucosa using de-epidermized dermis or AlloDerm Ò decreased overall degree of inflammation of the experimental wound through semi-quantitative analysis using H&E staining, yet did not support the data with additional quantitative measures.…”
Section: Discussion: Characterizing Oral Wound Healing In Emerging Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…86 On the other hand, Kiliç et al (2013) showed general increase in macrophage infiltration on Day 5 post-treatment with glutathione; however, this study lacked quantitative evidence besides H&E staining on the epidermis and lamina propria. 89 Couto et al (2016) studied the effects of applying bismuth subgallate in the buccal wounds of Wistar rat but results found a chronic inflammation status and a possible negative effect leading to delayed healing. 142 Similarly, Ophof et al (2008) stated that treatment with autologous mucosa using de-epidermized dermis or AlloDerm Ò decreased overall degree of inflammation of the experimental wound through semi-quantitative analysis using H&E staining, yet did not support the data with additional quantitative measures.…”
Section: Discussion: Characterizing Oral Wound Healing In Emerging Therapiesmentioning
confidence: 99%
“…89 Couto et al (2016) studied the effects of applying bismuth subgallate in the buccal wounds of Wistar rat but results found a chronic inflammation status and a possible negative effect leading to delayed healing. 142 Similarly, Ophof et al (2008) stated that treatment with autologous mucosa using de-epidermized dermis or AlloDerm Ò decreased overall degree of inflammation of the experimental wound through semi-quantitative analysis using H&E staining, yet did not support the data with additional quantitative measures. 143 Though most studies analyzed inflammatory infiltrates through histological staining, Ballestas et al (2019) additionally included flow cytometric data for quantitative analysis of immune infiltration around the ONF injury in the hard palate.…”
Section: Discussion: Characterizing Oral Wound Healing In Emerging Therapiesmentioning
confidence: 99%
“…Microscopically, angiogenesis within the tonsillar fossae commences from pre-existing vessels in the extracellular matrix, facilitating granulation tissue formation 38 . The granulation tissue further proliferates within the tonsillar fossae, often protruding beyond the pillars by day 5 34 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis within the tonsillar fossae commences from pre-existing vessels in the extracellular matrix, facilitating the formation of granulation tissue. 38 The granulation tissue further proliferates within the tonsillar fossae, often protruding beyond the pillars by day 5. 34,36 Continued oropharyngeal epithelial ingrowth from the periphery and epithelial contracture results in separation of the fibrinous clot by day 7, exposing the underlying granulation tissue, 34,36 often coinciding with a period of increased risk of secondary hemorrhage.…”
Section: Microscopicmentioning
confidence: 99%
“…Fonte: Autores. Na Tabela 2, apenas o estudo do Couto, et al 2016, relatou uma interação negativa referente a cicatrização após o uso do SB. Portanto, todos os outros estudos mostram que não houve interferência no reparo tecidual e indo de acordo com os estudos clínicos, mostrando que o uso do SB é seguro para hemostasia sem prejudicar no reparo tecidual.…”
Section: Luzzi Et Al (2018)unclassified